Ethically Aligned Artificial Intelligence: Investigating Algorithmic Bias, Human Identity, and Posthuman Ethics through a Data-Driven Philosophical Lens - Alyousef, Awad; Omari, Asem (Journal of Posthumanism, 2025)
Human society is being transformed by AI at an unprecedented speed-and in this context questions regarding fairness, agency, and identity become very tricky. This paper presents an interdisciplinary study into algorithmic bias and its ethical implicature in the relationship of data science and philosophy. By bringing into account concepts from posthumanism and moral theory, the research scrutinizes the redefinition of human identity within an age of autonomous systems and artificial consciousness. It proposes a data-oriented mechanism to the detection and mitigation of bias in AI systems, substantiated with case studies in health care and recruitment. One of the emphases of this work is on transparency, accountability, and inclusive governance, ultimately arguing for ethically aligned AI that promotes human dignity concurrent with evolving technological realities. Implications of this study point toward diversifying the development of a new ethical paradigm with the capability to regulate AI design, deployment, and policy.